ABUSE OF AUTHORITY IN GRANTING RELIEF ON MANAGEMENT RIGHTS LEVY (CASE STUDY OF CORRUPTION CRIMINAL ACTS IN SINGKAWANG CITY) - Riyan; Femmy Silaswaty Faried; Muhammad Aziz Zaelani (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study analyzes the abuse of authority in granting concessions on Management Rights (Hak Management/HPL) fees and identifies the factors causing deviations in the corruption case in Singkawang City. The research uses an empirical legal method supported by a normative approach through statutory, conceptual, and case-based analysis. Data were obtained from legislation, legal literature, case documents, media reports, and relevant institutional information. The results show that fee concessions may be legally justified when they are based on clear authority, objective parameters, written procedures, and accountable supervision. However, discretion becomes problematic when it is used without measurable standards, when the administrative process is incomplete, and when the decision reduces regional revenue or benefits for certain private parties. In the Singkawang case, the granting of a substantial reduction in HPL fees and the elimination of administrative penalties indicates the importance of distinguishing administrative error from corruption. The main causal factors include weak internal supervision, unclear limits on discretion, low transparency in regional asset management, weak compliance with legislation, and potential conflicts of interest. Strengthening preventive supervision, written technical guidelines, transparent documentation, and proportional law enforcement are therefore necessary to protect regional finances and support good governance.